Development of coaches training - Global trends - Bales, J. (1st International Council for Coach Education Asian Regional Coaching Conference, 2005)
Among the trends that are occurring in international sport that are having a significant impact on coaching and coach education are: - An explosion of sport events, with new sports and events, such as synchronized diving, cross country ski sprint, women`s wrestling, world youth championships and the growth in the Paralympics. While providing significant new opportunities, this is also increasing the demands on athletes and coaches. The competition calendar is becoming very crowded, more chief coaches are needed, and the stress caused by travel and performance demands needs to be addressed in coach education programs. Particularly with age group athletes, the emphasis on winning at international championships would appear to be causing burnout and an early exit from high performance sport: some studies have shown that less than 30% of the medal winners at the junior level go on to win senior world or Olympic medals. - Doping and ethical issues continue to be an important influence on the sport environment. World Anti-Doping Agency chair Dick Pound has proposed, on the recommendation of the IOC Athletes Commission, that athletes provide the names of both their physician and coach when being tested. This is prompting closer attention to the responsibilities of coaches in doping free sport and the need for coach education on the signs of doping behaviour and strategies to handle such behaviours. - Technology in sport has grown tremendously, and is influencing many aspects of coaching, from communication among athletes and coaches to game analysis to equipment modifications and applications of sport science. New skill sets are needed for coaches to be able to take advantage of these technologies, while not compromising the close working relationships between coaches and athletes. - Customized learning. Programs are expected to meet the specific needs of the learner, there is wide acceptance of the need for on-going learning (life long learning), and many programs are shifting to a competency-based approach, with a focus on practical, job-related requirements. For example, the IAAF is initiating specific programs for elite coaches, chief coaches and professional development coaches. - Business coaching has become a widespread practice, acknowledging the value of the coach in personal growth and team performance. The scope of coaching, and the opportunities for coaches, continues to grow. Within this constantly changing environment, the core stability of the coach must be maintained. The coach`s key role is to challenge individuals to grow, to create the environment for teams to perform, and to synthesize diverse areas of expertise into a coherent philosophy of excellence. Effective coaches are leaders, as defined by John Adams, "If your actions inspire others to dream more, learn more, do more and become more, you are a leader".